Innovation for sustainable entrepreneurship: Empirical evidence from the bioeconomy sector in Poland - Mariusz Sołtysik; Maria Urbaniec; Magdalena Wojnarowska (Administrative Sciences, 2019)
The growing importance of sustainable development, especially regarding environmental issues, contributes to shaping new trends at the level of enterprises. Sustainable development is perceived as a source of new entrepreneurial opportunities that serve to solve social and environmental problems. The main objective of this study is to identify factors supporting and hindering the development of enterprise innovativeness exemplified by the bioeconomy sector in Poland. A research analysis was based on the Entrepreneurial Discovery Process (EDP) model. The study employed the method of critical literature analysis, as well as qualitative methods, such as individual direct interviews with experts and smart labs with 252 enterprises from the economic sector. The results of the research analysis show that the innovative activity of enterprises in the bioeconomy sector depends on external, as well as internal, factors. This is particularly important, owing to the impact of enterprises on the environment and on society, as they contribute to the creation and implementation of new, more sustainable production and consumption models.
Keywords: 350; innovation; sustainable development; sustainable entrepreneurship; bioeconomy; cluster